Detection of circulating tumor cells as therapeutic markers in patients with penile squamous cell carcinoma: A preliminary study. Issue 1 (6th January 2022) - Kao, Chien-Chang; Xu, Ting; Yang, Yung-Ning; Tsai, Yi-Ta; Liu, Shu-Yu; Wu, Sheng-Tang; Meng, En; Tsao, Chih-Wei; Chen, Chin-Li; Sun, Guang-Huan; Yu, Dah-Shyong; Chang, Sun-Yran; et al.
Abstract : Background: This study aimed to investigate the presence of circulating tumor cells (CTCs) in patients with penile squamous cell carcinoma (PSCC). Methods: CTCs were isolated from 14 patients with PSCC, 6 patients with balanoposthitis, and 6 healthy individuals. CTCs were enriched based on cell surface markers and filtered through the IsoFlux device, followed by identification according to cell morphology and immunofluorescence studies. Results: CTCs were found in all PSCC blood samples but not in balanoposthitis samples and samples from healthy individuals. Immunofluorescence studies confirmed the tumor origin. When the patients with PSCC were stratified according to metastatic inguinal lymph node status, a statistically significant difference was observed in the number of detected CTCs. Conclusion: Our study showed that CTCs in PSCC may represent a valuable marker for differentiating PSCC from other tumors. Based on the correlation with some clinical parameters, CTC analysis is possibly relevant for noninvasive monitoring of disease progression and prognosis. The results also suggested a potential role of CTCs in preventing overtreatment, such as inguinal lymph node dissection.